(3YTQI eLGdS ef CeGdi GdNQais - (3YHO GdQMef Hf YHjO Gddg Hf YHO Gddg GdNQajs
(3ChdgG (B:s
(3CNHQfG CHh YHOGddg eMeO Hf EHQGgje Hf eSde Hf SdjeGf GdEQHjdi bQCg Ydjg hCfG CSeY s
(3BNQgG (B:s
(3Ke CbHd ai YQV GdfGS hgh jbhd jG NjQ ef OafJ HGdbGY CYXeg aWGH ef WjHI GdbHYGf hajg GdLhO hGdcQe s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdKGfis
(3eUOQ GbJfGA GdCUd (B:s
(3JhfS s
Keywords: (3GdMOjK h GdeUWdMs